Biochemical Studies of the Effects of Nauclea Latifolia Ethanolic Root Extracts in Rats - C, Udeh Sylvester M.; N, Ogugua V.; Y, Ojochenemi E.; J, Parker E.; S, Egba; E, Anaduaka; P, Ugwu O.; M, Ude C.; J, Iornenge T.; J, Danjuma (Darul Yasin Al Sys, 2024)
The plant Nauclea latifolia (Smith) (Family: Rubiaceae) also known as ‘Pin Cushion tree’ or ‘African Peach’ is a struggling shrub, native in tropical Africa and Asia where the use of folk medicine is preval_ent and the search for herbal cure is but common practice. Extraction of the root of Nauclea latifolia with ethanol yielded the ethanol extract. The acute toxicity study on the ethanol extract in mice established an intraperitoneal LD50 greater than 4000mg/kg. Thus, the ethanol extract could generally be regarded as safe. The phytochemical analysis of the Nauclea latifolia ethanol extract indicated the presence of flavonoids, saponins and reducing sugars. The result of the liver function test, alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase enzymes and the serum concentrations of conjugated and total bilirubin measured suggest mild damage of the liver hepatocytes of rats treated with ethanolic extract of Nauclea latifolia root when compared to the control. Increased serum enzyme concentrations could be associated with hepatocellular damage. The result of urea and creatinine indicate that the kidney may be damaged when compared to the control group. The extract caused a slight but non significant increase (p > 0.05) in blood glucose concentration as administration of the extract continued at days 28 and 42. The present study established that the continuous administration of the ethanol crude extract of Nauclea latifolia is lethal to the hepatocytes and kidneys.